Increased Levels of Soluble CD206 Associated with Rapidly Progressive Interstitial Lung Disease in Patients with Dermatomyositis. (28th October 2020) - Shen, Ya-Wen; Zhang, Ya-Mei; Huang, Zhen-Guo; Wang, Guo-Chun; Peng, Qing-Lin
Abstract : Objective . Soluble CD206 (sCD206) is considered a macrophage activation marker, and a previous study proved it as a potential biomarker to predict the severity of anti-melanoma differentiation-associated gene 5- (anti-MDA-5-) positive dermatomyositis- (DM-) associated interstitial lung disease (ILD). To investigate the role of sCD206 in various subtypes of DM, we evaluated the serum level of sCD206 in patients with different myositis-specific autoantibodies besides anti-MDA-5 and clarified its clinical significance. Methods . Commercial enzyme-linked immunosorbent assay kits were used to detect serum concentrations of sCD206 in 150 patients with DM and 52 healthy controls (HCs). Correlations between sCD206 levels and clinical features, laboratory examinations, and pulmonary function test parameters were analysed. Results . The median concentrations of serum sCD206 in DM patients were significantly higher than those in HCs (p < 0.0001 ). Furthermore, median sCD206 levels were elevated in patients with ILD (p = 0.001 ), especially in those with rapidly progressive ILD (RP-ILD) (p < 0.0001 ). In addition, sCD206 levels were negatively correlated with the pulmonary function test results, including the percent predicted forced vital capacity (r = − 0.234, p = 0.023 ), percent predicted forced expiratory volume in one second (r = − 0.225, p = 0.030 ), and percent predicted carbon monoxide diffusion capacity (r = − 0.261, p = 0.014 ). Age- and gender-adjusted multivariable analysis showed that sCD206 was an independent prognostic factor for RP-ILD in patients with DM. A longitudinal study showed that sCD206 levels were positively correlated with the physician global assessment visual analog scale scores (β = 54.201, p = 0.001 ). Conclusion . Serum sCD206 levels were significantly increased in patients with DM and significantly associated with RP-ILD, suggesting that sCD206 is an important biological predictor of RP-ILD in patients with DM.